Традиційне харчування волинян - Давидюк, М. (Народна творчість та етнографія, 2006)
The study of eating habits is an essential part of the investigation of national identity. The peculiarities of food reveal ethnic features vividly. The author speaks on the necessity of its research in complex. I he history of this topic is depicted in the work. A detailed study of agriculture, including its history, the most popular plants, and their spread are given. Stock-breeding and fishing are thoroughly described as well. Some notes are given on hunting and apiculture. Principles of processing and keeping of raw materials ate under a careful study. Finally, a wide range of traditional meals are described.